2014
DOI: 10.1007/s00425-014-2153-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide fungal stress responsive miRNA expression in wheat

Abstract: MicroRNAs (miRNAs) are small non-coding class of RNAs. They were identified in many plants with their diverse regulatory roles in several cellular and metabolic processes. A number of miRNAs were involved in biotic and abiotic stress responses. Here, fungal stress responsive wheat miRNAs were analyzed by using miRNA-microarray strategy. Two different fungi (Fusarium culmorum and Bipolaris sorokiniana) were inoculated on resistant and sensitive wheat cultivars. A total of 87 differentially regulated miRNAs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 46 publications
1
54
1
Order By: Relevance
“…Several miRNA families have been reported to be differentially regulated in response to drought stress in various plant species, including rice (Zhao et al 2007), tomato (Solanum lycopersicum , Arabidopsis (Liu et al 2008), Medicago truncatula (Trindade et al 2010), peach (Eldem, et al 2012), barley (Kantar et al 2010), and wheat (Gupta, et al 2014;Pandey, et al 2014). There are several studies documenting expression levels of various miRNAs in T. aestivum L. (Xin, et al 2010;Inal et al 2014;Pandey, et al 2014), but none of these miRNAs are experimentally verified. Moreover, the biological functions of miRNAs upon drought stress have been identified experimentally in plants, but the number of studies is very limited.…”
Section: Introductionmentioning
confidence: 95%
“…Several miRNA families have been reported to be differentially regulated in response to drought stress in various plant species, including rice (Zhao et al 2007), tomato (Solanum lycopersicum , Arabidopsis (Liu et al 2008), Medicago truncatula (Trindade et al 2010), peach (Eldem, et al 2012), barley (Kantar et al 2010), and wheat (Gupta, et al 2014;Pandey, et al 2014). There are several studies documenting expression levels of various miRNAs in T. aestivum L. (Xin, et al 2010;Inal et al 2014;Pandey, et al 2014), but none of these miRNAs are experimentally verified. Moreover, the biological functions of miRNAs upon drought stress have been identified experimentally in plants, but the number of studies is very limited.…”
Section: Introductionmentioning
confidence: 95%
“…However, there are several reports indicating that miRNAs from the MIR169 family are also involved in response to biotic and abiotic stresses (Sunkar et al 2012;Inal et al 2014;Luan et al 2015). Interestingly, under drought stress the wheat miR169 was highly downregulated in leaves but upregulated in roots (Akdogan et al 2016).…”
Section: Highly Conserved Wheat Mirnas Are Developmentally Regulatedmentioning
confidence: 99%
“…It has been suggested that miR169-dependent NF-YA regulation can be involved in response to stresses in A. thaliana and maize (Leyva-Gonzalez et al 2012;Nelson et al 2007;Pant et al 2009). Its implications in fungal response in wheat (Inal et al 2014), as well as in drought tolerance and stem sugar content, were also described (Calvino and Messing 2013). Additionally, miR169 is involved in nodule development and nutritional balance in legume plants (Simon et al 2009).…”
Section: Target Predictionmentioning
confidence: 99%